Epigenetic dysregulation of ACE2 and interferon-regulated genes might suggest increased COVID-19 susceptibility and severity in lupus patients - Sawalha, Amr H (Clinical immunology (Orlando, Fla.), 2020)
Copyright © 2020 Elsevier Inc. All rights reserved.